Value of coronary artery calcium score in reporting SPECT versus PET myocardial perfusion imaging. (20th July 2021) - Van Dijk, JD; Mouden, M; Van Dalen, JA; Jager, PL
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although it is well known that coronary artery calcium score (CACS) adds value to reporting myocardial perfusion imaging (MPI) SPECT, its added value to reporting PET MPI is not clear. Purpose: Hence, our aim was determine the value of adding CACS in the assessment of PET MPI and SPECT MPI and compare the value between both modalities in a low-risk population. Methods: We retrospectively included 412 patients, half of them underwent SPECT with CACS and half underwent Rubidium-82 PET with CACS. We created comparable groups using propensity matching, where the PET group was 1:1 matched to a comparable SPECT group, obtained from a large cohort of 4018. Next, we created two types of image sets for the 412 included patients: MPI-only and MPI + CACS. Two experienced physicians interpreted the 824 images as normal, equivocal or abnormal for  ischemia or irreversible defects and were blinded for the used modality. In addition, annualized event rates, defined as the occurrence of all-cause death, non-fatal myocardial infarction or revascularization therapy (PCI or CABG), were compared between the PET and SPECT groups using a follow-up period of 30 months. Results: The percentage of scans interpreted as normal was 8% higher with PET-only than with SPECT-only (89 vs 80%, respectively, p = 0.014). Adding CACS to SPECT increased the percentage of scans interpreted as normal from 80% to 86% (p = 0.014), whereas this effect was absent for PET (p = 0.77). Adding CACS reduced the frequency of equivocal scans from 12% and 6% to 0% for both SPECT and PET, respectively. Furthermore, adding CACS resulted in 5% more abnormal interpreted scans for both PET (4.9 to 10%, p = 0.003) and SPECT (8.7 to 14%, p = 0.04). The annualized event rate was 2.7% for the SPECT and 3.5% for the PET group (p = 0.58). The annualized event rates for images interpreted as normal were comparable between all four types of image sets and varied between 0.7-2.0% (p > 0.084). The annualized event rate for equivocal and abnormal scans was higher for PET-only (23%) compared to SPECT-only (4.8%, p < 0.001). Moreover, the event rate for equivocal and abnormal SPECT + CACS  (8.6%) was also higher than for SPECT-only (4.8%, p = 0.04), whereas this difference was absent for PET (p = 0.07). Conclusion: Adding CACS increases the percentage of scans interpreted as normal for SPECT MPI while the event rate remained unchanged. Adding CACS to PET did not influence the percentage of scans interpreted as normal, limiting the effect of adding CACS to PET in a low-risk population.